Respostas
respondido por:
0
a) 16x⁴
b) 4x^6
c) +9x²
d) -8x³
e)(4x²).(4x²) = 16x⁴
f) (2x³).(2x³) = 4x^6
g)(-3x).(-3x) = +9x²
h)(-2x).(-2x).(-2x) = -8x³
espero que tenha entendido
b) 4x^6
c) +9x²
d) -8x³
e)(4x²).(4x²) = 16x⁴
f) (2x³).(2x³) = 4x^6
g)(-3x).(-3x) = +9x²
h)(-2x).(-2x).(-2x) = -8x³
espero que tenha entendido
respondido por:
0
a) 16x⁴
b) 4x^6
c) 9x²
d) -8x³
e) 16x⁴
f) 4x^6
g) 9x²
h) -8x³
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás